The Matrimonial Maidens of downry for familiar and affective bows in three sevillian hospitals the old regime (Estudios de Historia de España, 2019)
The noble families protected the female surplus from their lineages, destining to this end testamentary wills, some of which were kept per centuries. Nevertheless not only they tried to protect to their own lineage, but to elite women which families had fallen down in misfortune. They tried to protect the lineage of the people they loved as maids and slaves. In the Sevillian capital, the hospitals of the Mercy, of Five Sores and of San Hermenegildo were managers of these wills and in this article discover how administrated those effective and consanguineous dowries.
Keywords: Hospitals; Dowry; Marriage; Hidalgas; Sevilla; Old Regime